Chapter Comunità online e sviluppo professionale degli insegnanti: riflessioni sul caso di eTwinning nel quadro di un approccio data-informed - Gabbi, Elena (Studies on Adult Learning and Education, 2022)
This paper investigates the potential of data-mediated reflective practice for teachers, members of the eTwinning professional community, within a research strategy that explores big data in education. The chapter begins by emphasising the potential of online communities for the professional development of teachers. It provides an example of a qualitative research method used, in conjunction with a data-driven strategy in order to identify significant challenges and recommendations for the advancement of the eTwinning online community in Italy. Finally, it focuses on the analytical explanation of the findings and offers some concluding remarks on the significance of the emerging development dimensions.